2022
DOI: 10.1001/jamasurg.2022.0631
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Quality of Life in Patients With Breast Cancer After Breast Conservation vs Mastectomy and Reconstruction

Abstract: IMPORTANCETreatment options for early breast cancer include breast-conserving surgery with radiation therapy (RT) or mastectomy and breast reconstruction without RT. Despite marked differences in these treatment strategies, little is known with regard to their association with long-term quality of life (QOL).OBJECTIVE To evaluate the association of treatment with breast-conserving surgery with RT vs mastectomy and reconstruction without RT with long-term QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 43 publications
1
45
0
1
Order By: Relevance
“…It is estimated that about 287,850 females have suffered from breast cancer and approximately 43,250 patients have died from the cancer in 2022 so far (1). With advancements in surgery, chemotherapy, radiation, and hormone therapy, the survival of breast cancer has been improved in the past few decades (2)(3)(4). The improvement of multimodal therapies is significant for the survival of cancer patients, with a 5-year relative survival over 90% in developed countries (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 287,850 females have suffered from breast cancer and approximately 43,250 patients have died from the cancer in 2022 so far (1). With advancements in surgery, chemotherapy, radiation, and hormone therapy, the survival of breast cancer has been improved in the past few decades (2)(3)(4). The improvement of multimodal therapies is significant for the survival of cancer patients, with a 5-year relative survival over 90% in developed countries (5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients with this type of tumor are at potentially high risk of ipsilateral or contralateral recurrence, and risk-reduction mastectomy is strongly considered in patients with BRCA1 mutation 57 . However, an investigation of long-term patient-reported outcomes after surgical treatment of early-stage breast cancer showed equivalent patient satisfaction with their breasts and physical well-being, but better psychosocial and sexual well-being, in patients who underwent breast-conserving surgery with subsequent radiation therapy compared with patients who underwent mastectomy and reconstruction 58 . Using a 4T1 local recurrence model, we successfully showed that the depletion of MGTRMs by CL treatment at tumor resection significantly reduced local recurrence and distance metastases, and enhanced the chemotherapeutic outcome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation of long-term patient-reported outcomes after surgical treatment of early-stage breast cancer, Hanson et al reported equivalent patient satisfaction with breasts and physical well-being but better psychosocial and sexual well-being in patients who underwent breast-conserving surgery with subsequent radiation therapy (RT) compared with patients who underwent mastectomy and reconstruction. Given that more women eligible for breast-conserving surgery are choosing to undergo mastectomy, these findings have important implications for those patients’ decisions.…”
mentioning
confidence: 99%
“…However, most prior studies included patients undergoing breast-conserving surgery without RT, patients undergoing mastectomy without reconstruction, and patients undergoing mastectomy with RT. The study by Hanson et al directly compared breast-conserving surgery with RT vs mastectomy and reconstruction without RT to avoid those potential confounders. One area not explored by Hanson et al is how breast-conserving surgery and mastectomy impact postoperative patient-reported outcomes compared with the preoperative baseline.…”
mentioning
confidence: 99%
See 1 more Smart Citation